Preservation of goat semen at 5°C with emphasis on its freezability and the impact of melatonin - El-Battawy KA (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
The success of an artifi cial insemination (AI) program depends on the proper management of semen collection, storage and use. Goat semen has been stored at temperatures ranging from 2 to 15°C and mostly at 5°C using various diluents such as sodium citrate-yolk, sodium citrate-fructose-yolk, milk (whole, skimmed or reconstituted) with or without egg yolk, Spermasol, Neoseminan, saline [1]. It was found that trisbuffer extenders were effective for dilution and storage of goat, sheep and rabbit semen [2-4]. Nishikawa et al., [5], stored goat spermatozoa in Neoseminan diluent at 4°C for 8-15 days and maintained their fertilizing capacity for 6 days.Moreover, Eppleston et al., [6], demonstrated that goat spermatozoa have retained their fertilizing capacity for at least 8 days of storage at 5°C in Tris- Fructose-citric acid-yolk diluent.